Strategi pengembangan ekowisata Danau Masjid Kabupaten Kuantan Singingi - Irfan Yunus; Zulfan Saam; Yusni Ikhwan Siregar (Jurnal Zona, 2019)
Masjid Lake is one of the Natural Tourism Objects in Riau Province, which is located in Kuantan Singingi Regency. This research is intended to determine the potential condition of the Koto Kari Mosque Lake area and its feasibility to be developed as an ecotourism object, identify and analyze tourist attractions, amenities and accessibility of ecotourism development, analyze the economic impact on ecotourism development, and formulate ecotourism development strategies in the Danau Masjid Regency area. Kuantan Singingi. The research method is a survey method by conducting direct field observations accompanied by interviews with the Kuantan Singingi Regency Government as managers, traditional and religious leaders. Traditional and religious leaders were used as representatives of the community to fill out the questionnaire. Respondents consisted of four traditional leaders and one religious leader, and the sampling was conducted at three station locations in the north, west and east which were seen based on differences in characteristics possessed in the tourist area of the Koto Kari Mosque Lake. To obtain an overview of the strategy to be used, an analysis was carried out with several stages and was guided by the FMU development design model S and the formulation of strategies from the data and information obtained were analyzed using the SWOT method, namely by analyzing internal and external factors owned by the Danau Mesjid Koto area. Curry. The results showed that the suitability of Koto Kari Mosque Lake tourism, at Station 1 which is located in the northern part, is categorized as suitable for all tourism activities, namely fishing (94.12%), camping (86.27%), water games (90.20%). , sit back (91.67%) and outbound (78.43%) this is because this location has a depth of 1-2 m, slope kurang dari 200, clarity lebih dari 80%, calm water, the view seen at this station is a stretch lakes, rice fields and rubber gardens. Whereas Station 2 in the western part has the appropriate conditional criteria for fishing tourism activities (94.12%) and sitting back (90.20%), because this location has a narrow lakeside and the historical building of the Old Koto Kari Mosque and residential housing in the outskirts of the lake, and at station 3 which is located in the eastern part are suitable for outbound activities, sitting back and camping with the percentage of 91.67%, 90.20% and 86.27%, respectively. Based on observations and referring to the opinion of the local community, the lake waters have characteristics that are deep enough to be dangerous for boating and water games. Based on the results of the analysis of the carrying capacity in the Koto Kari Mosque Lake area, it is different at each station location. Station 1 based on the calculation of the Tourism Suitability Index value of this station is very suitable for fishing, camping, water games, sitting back and outbound, while station 2 is very suitable for fishing and sitting back, and at station 3 is suitable for outbound activities, sitting back and camping. . The results of the analysis of area management strategies for ecotourism using SWOT analysis resulted in 9 alternative strategies, but those that can be used as a top priority as a strategic plan for the development of the Koto Kari Mosque Lake tourism area, namely holding cooperation in promoting the Koto Kari Mosque Lake as a natural and sustainable tourism area. its resources, attracting investors for the development of Koto Kari Mosque Lake tourism while still paying attention to the preservation of its resources, as well as coordinating in overcoming problems and threats that exist in the Koto Kari Mosque Lake